Sensory-directed flavor analysis of key odorants compounds development of French fries and oils in the break-in, optimum and degrading frying stage - Lirong Xu; Gangcheng Wu; Jianhua Huang; Hui Zhang; Qingzhe Jin; Xingguo Wang (Food Science and Human Wellness)
The flavor is a decisive sensory characteristic that determines the popularity of French fries (FFs). During high-oleic rapeseed oil (RO) frying, the flavor development of FFs showed three noticeable stages including break-in (3.5 %–7.5 % of total polar compounds (TPC)), optimum (7.5 %–22.18 % of TPC), and degrading stages (above 22.18 % of TPC). Further, in order to distinguish the key aroma compounds in each stage, the FFs prepared in RO at TPC of 3.5 % (FF4), 14.5 % (FF15), and 26.96 % (FF27) and their relevant oils (RO4, RO15, RO27) were selected for sensory-directed analysis. The results revealed that the FF4 had low contents of (E,E)-2,4-decadienal (deep-fried odor) which also caused lower sensory score in FF4 sample. The higher contents of (E,E)-2,4-decadienal in FF15 induced its higher deep-fried odor. The FF27 had higher hexanoic acid (sweaty odor), heptanoic acid, nonanoic acid, benzene acetaldehyde (stale odor), and trans-4,5-epoxy-(E)-2-decenal (metallic odor) compared with FF4 and FF15, thus leading to the undesirable flavor of FF27. Moreover, the decrease of 2,5-dimethylpyrazine and 2-ethyl-6-methyl-pyrazine in FF27 induced the lower roasty flavor, which may also lead to the decline of the sensory score. Similarly, the higher contents of (E)-2-undecenal, hexanoic acid, heptanoic acid, and nonanoic acid in RO27 lead to increase its rancid score and thus lower the sensory score.